India in the mirror of foreign diplomatic archieves - Zins, Max Jean 1947-; Boquérat, Gilles (Manohar Centre de Sciences Humaines, 2004)
On the foreign policies of United States of America and few other Developed countries of the world towards India; contributed articles presented earlier at a seminar.